Public Sector Balance Sheet Database : Overview and Guide for Compilers and Users - Alves, Miguel (IMF Working Papers; Working Paper ;, 2020)
This paper provides an overview of the Public Sector Balance Sheet (PSBS) Database, a dataset developed in the context of the October 2018 Fiscal Monitor. The dataset provides a comprehensive picture of public wealth for 38 countries, and a narrower picture for further 37 countries and territories. Comprehensive PSBSs bring together all the accumulated assets and liabilities that governments control, including public corporations, natural resources, and pension liabilities. They therefore account for the entirety of what the state owns and owes, offering a broader fiscal picture beyond debt and deficits. This is particularly relevant in the current context of record and still rising debts and heightened risks to the balance sheet of the public sector. PSBSs bring about greater transparency and allow closer scrutiny of government's financial position. They also allow better balance sheet management, thereby potentially increasing return on assets, reducing risks and the costs of borrowing, and improving fiscal policymaking. The paper also elaborates on the conceptual framework and methodology used in compiling the data, and provides some practical guidelines on the compilation, validation, and dissemination of such data.